2005
DOI: 10.1002/cne.20537
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor‐mediated collateral sprouting of central sensory axons into deafferentated regions of the dorsal horn is enhanced in the absence of the p75 neurotrophin receptor

Abstract: This study examined the growth capacity of nerve growth factor (NGF)-responsive dorsal root ganglion (DRG) central processes using mice of the following genotypes: wildtype, p75 neurotrophin receptor (p75NTR) exon III null mutant, NGF transgenic, and NGF transgenic with p75NTR exon III null mutation (NGF/p75(-/-)). In wildtype and p75NTR exon III null mutant mice calcitonin gene-related peptide (CGRP) immunoreactivity in the dorsal horn is dramatically reduced at both 3 and 28 days after rhizotomy. NGF transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Previous studies have suggested a role for p75 NTR in both restraining and facilitating axonal growth in the dorsal horn after dorsal rhizotomy, spinal cord injury and during development (Hannila and Kawaja, 2005;Scott et al, 2005). p75 NTR expression and upregulation with CYPinduced cystitis in the lumbosacral DH may represent central projections of sensory neurons, terminals of projection neurons, and/or descending p75 NTR systems (Pioro and Cuello, 1990;Sobreviela et al, 1994) exhibiting p75 NTR -IR, whereas interneuronal expression of p75 NTR is less likely (Bothwell, 1995).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies have suggested a role for p75 NTR in both restraining and facilitating axonal growth in the dorsal horn after dorsal rhizotomy, spinal cord injury and during development (Hannila and Kawaja, 2005;Scott et al, 2005). p75 NTR expression and upregulation with CYPinduced cystitis in the lumbosacral DH may represent central projections of sensory neurons, terminals of projection neurons, and/or descending p75 NTR systems (Pioro and Cuello, 1990;Sobreviela et al, 1994) exhibiting p75 NTR -IR, whereas interneuronal expression of p75 NTR is less likely (Bothwell, 1995).…”
Section: Discussionmentioning
confidence: 93%
“…Although numerous studies have suggested a central or peripheral role for p75 NTR after axotomy (Wakabayashi et al, 1998;Keast and Kepper, 2001;Hannila and Kawaja, 2005;Scott et al, 2005;Obata et al, 2006) or peripheral somatic inflammation (Cho et al, 1996;Pezet et al, 2001;Chien et al, 2007), few studies have examined the role of p75 NTR in normal or inflamed lower urinary tract pathways (Wakabayashi et al, 1996(Wakabayashi et al, , 1998(Wakabayashi et al, , 2002Vaidy- anathan Elsasser-Beile et al, 2000;Jahed and Kawaja, 2005;Tong and Cheng, 2005). To our knowledge, no studies have examined changes in p75 NTR expression in central or peripheral micturition reflex pathways after bladder inflammation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Whereas it is known that p75 NTR expression can enhance TrkA-NGF binding in some systems (1,9), p75 NTR may also reduce NGF-TrkA signaling by sequestering NGF (19,31,46). In the latter instance, any decrease or perturbation in NGF/ p75 NTR binding may tip the homeostatic equilibrium, resulting in increased NGF bioavailability to enhance NGF/TrkA signaling.…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of the p75 NTR in proliferating satellite glia in the injured dorsal root ganglion (DRG) correlates with the appearance of sympathetic sprouting which is attenuated in p75 NTR null mice (Hannila and Kawaja, 2005). In studies of motor neuron injury, less motor neuron survival was seen after the introduction of grafted Schwann cells deficient in p75 NTR (Tomita et al, 2007).…”
Section: Figure 1 Potential Signaling Partners Of the P75 Neurotrophimentioning
confidence: 98%